Perfectionist Liberalism and Political Liberalism (Part I) - Nussbaum, Martha C. (2016)
In the first part of this article, the author discusses two types ofliberalism from the thoughts of prominent philosophers. On the one hand, sheanalyzes the ideas of Isaiah Berlin and Joseph Raz as examples of perfectionistliberalism and, on the other, those of John Rawls and Charles Larmore asexamples of political liberalism. It also identifies differences between Berlin’spluralism and Raz’s and between Rawls’ liberalism and Larmore’s.